Abstract

No abstract available.

Full Article  |  PDF Article

References

  • View by:
  • |
  • |

  1. J. D. Gaskill, Linear Systems, Fourier Transforms, and Optics (Wiley, New York, 1978), Chap. 10.
  2. See, for example, J. Gotz, A. Lohmann, “TV-On Line-Generation of Pseudo-Stereo-Images,” Angewandte Optik Annual Report (1980), p. 40.
  3. See, for example, B. Julesz, Foundations of Cyclopean Perception (U. Chicago Press, Chicago, 1971).

Gaskill, J. D.

J. D. Gaskill, Linear Systems, Fourier Transforms, and Optics (Wiley, New York, 1978), Chap. 10.

Gotz, J.

See, for example, J. Gotz, A. Lohmann, “TV-On Line-Generation of Pseudo-Stereo-Images,” Angewandte Optik Annual Report (1980), p. 40.

Julesz, B.

See, for example, B. Julesz, Foundations of Cyclopean Perception (U. Chicago Press, Chicago, 1971).

Lohmann, A.

See, for example, J. Gotz, A. Lohmann, “TV-On Line-Generation of Pseudo-Stereo-Images,” Angewandte Optik Annual Report (1980), p. 40.

Other (3)

J. D. Gaskill, Linear Systems, Fourier Transforms, and Optics (Wiley, New York, 1978), Chap. 10.

See, for example, J. Gotz, A. Lohmann, “TV-On Line-Generation of Pseudo-Stereo-Images,” Angewandte Optik Annual Report (1980), p. 40.

See, for example, B. Julesz, Foundations of Cyclopean Perception (U. Chicago Press, Chicago, 1971).

Cited By

OSA participates in Crossref's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Alert me when this article is cited.


Figures (3)

Fig. 1
Fig. 1

Receding bright line as seen through a diffraction grating.

Fig. 2
Fig. 2

Scheme of the imaging optical system.

Fig. 3
Fig. 3

(a) Experimental setup for stereo-pair recording. (b) Stereo pair between the zero and first diffraction orders.

Equations (5)

Equations on this page are rendered with MathJax. Learn more.

u ( x , y ) = C ( z 13 z 12 ) 2 q [ x , y ; 1 λ z 34 ( 1 z 13 z 23 z 12 z 34 ) ] × T ( z 13 x λ z 12 z 34 , z 13 y λ z 12 z 34 ) ,
t ( x , y ) = A + B cos ( 2 π f 0 x ) ,
T ( z 13 x λ z 12 z 34 , z 13 y λ z 12 z 34 ) = A δ ( z 13 x λ z 12 z 34 , z 13 y λ z 12 z 34 ) + B δ ( z 13 x λ z 12 z 34 f 0 , z 13 y λ z 12 z 34 ) + B δ ( z 13 x λ z 12 z 34 + f 0 , z 13 y λ z 12 z 34 ) = A | λ z 12 z 34 z 13 | δ ( x , y ) + B | λ z 12 z 34 z 13 | × [ δ ( x λ z 12 z 34 z 13 f 0 ) + δ ( x + λ z 12 z 34 z 13 f 0 ) ]
δ ( z 13 x λ z 12 z 34 f 0 ) = 1 | z 13 λ z 12 z 34 | δ ( x f 0 z 13 λ z 12 z 34 ) ,
D = λ z 12 z 34 z 13 f 0 = λ z 12 z 34 z 12 + z 23 f 0 = ( λ z 34 f 0 ) ( z 12 / z 23 ) ( 1 + z 12 / z 23 ) = K ( z 12 / z 23 ) ( 1 + z 12 / z 23 ) ,

Metrics